(untitled) (Journal of Atomic and Molecular Sciences, 2017)
Using two-dimensional classical ensemble method, a theoretical study of non-sequential double ionization (NSDI) with Krypton (Kr) and carbon dioxide (CO_2) is presented at different laser intensities. The numerical results show that the probability for NSDI of Kr atom is higher than that of CO_2 molecule. Moreover, for the same laser intensity, the momentum correlation spectrum of CO_2 molecule is drastically different from Kr atom. For example, for the laser intensities I = 0.065 PW ⁄ cm^2 and I =0.15 PW ⁄ cm^2, the correlation spectrum of CO_2 molecule tends to distribute in the first and third quadrants, and presents a "finger-like" structure. However, for Kr atom at I = 0.065 PW ⁄ cm^2, the emitted electrons pairs tend to distribute in the second and fourth quadrants; When the laser intensity increases to 0.15PW ⁄ cm^2, the two electrons mainly distribute in the first and third quadrants and along two distinct lines being paralleled to the diagonal. In addition, our numerical calculations reveal that this different phenomenon is closely related to the Coulomb focusing effect: Coulomb potential will attract the returning electron more dramatically when it moves near the atomic or molecular core. For CO_2 molecule, the returning electron is dramatically attracted by three cores, so the returned electron of CO_2 molecule possesses higher energy than Kr atom does.